Interoperability of public information systems: challenge and strategy for colombian administration (2015)
This essay on the importance of interoperability of information systems of the Colombian public sector constitutes a review of the importance of information for decision-making, as well as the current status of developments in this subject at country level and its relevance with regard to transparency and accountability in governance. This reflection arises because currently the interoperability of information systems in the public sector appears as a challenge and a strategy to be followed by public administration in the framework of governance to venture interoperational and position in the globalized world and the case of Colombia in the near future have the opportunity to be part of the Organization for Economic Cooperation and Development - OECD. To highlight the importance of right use of public financial information in a globalized world that increasingly requires the management of institutions be standardized, not only in the field of country but a continent and worldwide. Colombia has shown significant progress but there are still many tasks to fulfill: agreements and unification of criteria between the budget and accounting bodies of the country and expanded coverage in response to the requirements of multilateral organizations.